Effects of Voids Towards Electric Field in High Voltage Cable - Ahmad Kamal, Nur Afifi Nadhirah; Muhammad Saufi Kamarudin (Evolution in Electrical and Electronic Engineering, 2022)
This paper presents a study and analysis of the effects of voids on electric fields in high voltage cables. The main objectives were to determine the electric field distribution at contaminated XLPE cable by designing the model of the cable using simulation software and to evaluate the effect of the location of voids using different materials of voids toward the electric field in the cable. The goal of this research is to explore the electric field in insulation containing a void as it is affected by the position of the void and the type of material utilised. The investigation of electric field gives a view on the performance of XLPE as an insulator as its existence may shorten the life span of cable. As the result, Other than using different materials of a void, each material has been tested on its different distance of void from the conductor at 12mm, 14mm and 16mm. Consequently, the relationship of a different material of void with the effects of the electrical field is set up such that is random. All of the different materials used in the cable, aluminium oxide (Al₂O₃) showed the least electric field. Decrement of electric field gives a view that this material can be used as nanofillers at optimum size.